Identifying the Leadership Challenges of K-12 Public Schools During COVID-19 Disruption: A Systematic Literature Review - Parveen, Khalida; Tran, Phuc Quang Bao; Alghamdi, Abdulelah A.; Namaziandost, Ehsan; Aslam, Sarfraz; Xiaowei, Tian (Frontiers in Psychology, 2022)
Globally, the COVID-19 pandemic is triggering a public health emergency and crisis on a large scale, with far-reaching effects and severe damage to all aspects of politics, economy, cultural and social life, and health. Consecutive outbreaks over the past nearly two years of ‘living with COVID-19’ have forced most schools to physically close, resulting in the largest educational disruption in human history. In turbulent times of the COVID-19 crisis, school leaders are facing numerous major challenges germane to school governance and leadership. The key objective of the study is to fully explore the prospective challenges principals are encountering in public schools in times of COVID-19. To fulfill the research purpose, a systematic literature review (SLR) was carried out to investigate the leadership challenges. As a result, a total of 24 challenges were explored through SLR approach. Frequency analysis approach was initially applied to figure out the most significant challenges. Accordingly, seven challenges were found statistically significant as showing frequency ≥50 each. Irrevocably, the study works as a contribution to K-12 school leadership by providing guidance for current and future leaders in crisis based on practical investigation, experiences, and recommendations. Policy makers can leverage these findings to make necessary adjustments to school policy to better prepare school leaders for crisis. Additionally, the findings of the current study are believed to have profound implications for future research. These findings expand our current understanding on school leadership in time of crisis that needs further investigation. Subsequent studies can quantitatively and/or qualitatively validate these leadership challenges findings regarding a particular school context.